3D reconstructions using GPR data at the Mont Beuvray - Timár, Lőrinc; Czajlik, Zoltán; Puszta, Sándor; Holl, Balázs (Dissertationes Archaeologicae, 2013)
This short case study had the aim to show a possible use of 3D visualization of ground penetrating radar (GPR) results. GPR’s main advantage over magnetometry is the presence of data related to the depth of the structures under the soil. This feature could be easily exploited using CAD applications and the results provide a great help for the evaluation of the GPR results.